2009
DOI: 10.1128/aem.00391-09
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli O157:H7 Strain Origin, Lineage, and Shiga Toxin 2 Expression Affect Colonization of Cattle

Abstract: Enterohemorrhagic Escherichia coli O157:H7 has evolved into an important human pathogen with cattle as the main reservoir. The recent discovery of E. coli O157:H7-induced pathologies in challenged cattle has suggested that previously discounted bacterial virulence factors may contribute to the colonization of cattle. The objective of the present study was to examine the impact of lineage type, cytotoxin activity, and cytotoxin expression on the amount of E. coli O157:H7 colonization of cattle tissue and cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…The difference may be explained by recent reports describing the importance of genotypic and phenotypic heterogeneity of STEC O157 for virulence and adaptation to the host environment. Lowe et al (18) and Zhang et al (37) showed higher levels of adherence to intestinal cells and Shiga toxin production in LI strains than in LII strains. For stx genotypes, many researchers have found a correlation between the stx 2 gene and disease severity in humans (3,5,19).…”
Section: Discussionmentioning
confidence: 96%
“…The difference may be explained by recent reports describing the importance of genotypic and phenotypic heterogeneity of STEC O157 for virulence and adaptation to the host environment. Lowe et al (18) and Zhang et al (37) showed higher levels of adherence to intestinal cells and Shiga toxin production in LI strains than in LII strains. For stx genotypes, many researchers have found a correlation between the stx 2 gene and disease severity in humans (3,5,19).…”
Section: Discussionmentioning
confidence: 96%
“…This corresponds to the mounting evidence that suggests there is considerable phenotypic diversity among animal-and human-associated isolates. E. coli O157 strains of animal origin showed much higher colonization of cattle tissue and cells in vitro than human-origin strains (41). The average acid resistance of bovine-biased genotypes was significantly higher than that of human strains (56,63), and bovine-biased genotypes are equipped with a more efficient nitrogen regulatory response system that enhanced survival under ammonia-limiting conditions (63).…”
Section: Resultsmentioning
confidence: 97%
“…There is one case report documenting a chronic STEC infection in a weaning kid [34] with the adherent pathogen identified as E. coli O103:H2, a non-O157 STEC that produced Stx. In the current study, we describe O157 and non-O157 STEC infections in adult goats with the non-O157 STEC requiring a 100 times lower exposure dose when compared with the O157 STEC to achieve the same colonization [33,35]. This is a remarkable virulence factor that may have contributed to the rapid onset of symptoms observed in the goats.…”
Section: Discussionmentioning
confidence: 93%